Кристалiзацiя карбонату кальцiю з гiдрокарбонатних розчинiв - Kochmarskii, V. Z.; Gayevskii, V. R.; Tyshko, N. L. (Publishing house "Academperiodika", 2018)
The kinetics of CaCO3 precipitation from model solutions formed by preliminary saturating deionized water with CO2 and by adding NaHCO3 and CaCl2 has been considered. The characteristic feature of the method is the almost simultaneous measurement of the activities of major components of the aqueuos calcium hydrocarbonate system (ACHCS): Ca2+, CO2, HCO−3 , as well as pH and the temperature. CaCO3 crystallization was provided with the help of the CO2 degassing by air. The processes running in the ACHCS during the degassing can be divided into four stages: dissociation of CaHCO+3 complexes; formation of crystal nuclei in the solution; a transitive stage, which includes the final phase of crystal nucleation and the initial growth of newly formed crystals; and intensive growth of crystal nuclei, which gives rise to the mass CaCO3 precipitation. The product (Ca2+)·(CO2−3 ) is a reaction coordinate for the second stage of CaCO3 precipitation, whereas (Ca2+)·(HCO−3 ) for the third and fourth stages. The kinetics of growth of crystal nuclei and their concentration are calculated for the second stage, by using the concept of CaCO3 dissolution product that depends on the crystal nucleus size. During the process of crystal nucleation, the crystal size remains practically stable (≈8×10^−8 m), and the concentration reaches 1.5×10^−15 m−3. The mass CaCO3 precipitation (the fourth stage) starts when the crystal nuclei reach dimensions of about 3×10^−7 m.